Histomorphometric analysis of gingival tissue in smokers and nonsmokers - Mundoor Manjunath Dayakar; Jitendra Kumar; Gurpur Prakash Pai; Srikant Natarajan (SRM Journal of Research in Dental Sciences, 2015)
Background: Smoking has been recognized as a major risk factor for periodontal diseases. Periodontal diseases are known to cause inflammatory vascular and epithelial changes in the gingiva on its own even in the absence of smoking. Hence, the present study is conducted to compare the epithelial and vascular changes in the gingiva of smokers and nonsmokers suffering from chronic periodontitis. Aim of Study: The purpose of this study was to evaluate and compare the epithelial and microvasculature changes in the gingiva of smokers and nonsmokers with chronic periodontitis. Materials and Methods: The study population consisted of 15 smokers and 15 nonsmokers. Gingival tissue biopsies with diameter of 5 mm including both epithelium and connective tissue were harvested from periodontal surgical sites and sent for histopathological examination. The images of the histological section were interpreted using ImageJ analyzer system. Statistical Analysis: Student′s t-test was used to compare the results. Results: Mean area of lumen and blood vessel density among smokers was lesser than nonsmokers, and thickness was found to be more in nonsmokers. Conclusion: The present study concludes that mean thickness of gingival epithelium, mean blood vessel density and lumen area were higher in nonsmokers compared to smokers. Percentage of small-sized and medium-sized blood vessels was higher in smokers.